2012
DOI: 10.5402/2012/898051
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength and Setting Time of MTA and Portland Cement Associated with Different Radiopacifying Agents

Abstract: Objective. The aim of this study was to evaluate the compressive strength and setting time of MTA and Portland cement (PC) associated with bismuth oxide (BO), zirconium oxide (ZO), calcium tungstate (CT), and strontium carbonate (SC). Methods. For the compressive strength test, specimens were evaluated in an EMIC DL 2000 apparatus at 0.5 mm/min speed. For evaluation of setting time, each material was analyzed using Gilmore-type needles. The statistical analysis was performed with ANOVA and the Tukey tests, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
(52 reference statements)
3
19
0
Order By: Relevance
“…According to Islam et al,33 this is due to the continuous setting of material, which leads to increased strength and stability. A 24-hour compressive strength of angelus MTA in this study is consistent with the study of Kogan et al 41 The 24-hour and 30-day compressive strengths of angelus MTA in the study are not consistent with the studies of Chung et al 44 and Tanomaru-Filho et al 45 In the study of Chung et al, 44 MTA compressive strength in 24 hours has been reported to be about 18 MPa, which is much lower compared with the number reported in our study (30 MPa). There are differences in the test method: plastic generators with a diameter of 4 mm and a height of 8 mm each have been used in that study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…According to Islam et al,33 this is due to the continuous setting of material, which leads to increased strength and stability. A 24-hour compressive strength of angelus MTA in this study is consistent with the study of Kogan et al 41 The 24-hour and 30-day compressive strengths of angelus MTA in the study are not consistent with the studies of Chung et al 44 and Tanomaru-Filho et al 45 In the study of Chung et al, 44 MTA compressive strength in 24 hours has been reported to be about 18 MPa, which is much lower compared with the number reported in our study (30 MPa). There are differences in the test method: plastic generators with a diameter of 4 mm and a height of 8 mm each have been used in that study.…”
Section: Discussionsupporting
confidence: 74%
“…In the study of Tanomaru-Filho et al, 45 24-hour and 21-day strengths are roughly half the amount reported in our study. There were differences in the method of experiments with this study.…”
Section: Discussionsupporting
confidence: 47%
“…However, it is related that this substance interferes with the hydration mechanism of MTA and calcium hydroxide precipitation in the hydrated cement 7) . Furthermore, the association of BO changes the microstructure of the cement matrix 8) , and increases the porosity and solubility of the Portland cement reducing its resistance 8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…Also, ZrO2 associated with PC presents radiopacity, compressive strength, setting time, water absorption and solubility similar to ProRoot MTA ®13) . TanomaruFilho et al 9) evaluated the compressive strength and setting time of MTA and PC associated with bismuth oxide, ZrO 2, calcium tungstate, showing that all radiopacifying agents may be used in association with PC to replace bismuth oxide. Camilleri et al 14) reported that the hydration reaction of 30% of ZrO2 added to PC produces calcium silicate hydrate, calcium hydroxide and a minimum amount of monosulfate and ettringite (hydrous calcium aluminum sulfate mineral) and, thus, does not affect the hydration mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Although radiopacifiers are not reagents of the hydration setting reaction, they can change or impede the setting reaction leading to some changes to the physical properties of the set cement (40)(41)(42). The choice of radiopacifier has other implications, including whether the cement darkens over time or causes darkening of adjacent tooth structure, such as when bismuth oxide is used (43).…”
Section: Radiopacifiermentioning
confidence: 99%